2021
DOI: 10.18332/tid/132290
|View full text |Cite
|
Sign up to set email alerts
|

Social deprivation and secondhand smoke exposure among urban male residents: A nationwide study in China

Abstract: INTRODUCTION Social deprivation is a known determinant of health and related behaviors. Many studies have linked socioeconomic factors to secondhand smoke (SHS) exposure. However, no studies have examined the relationship between social deprivation and SHS exposure. This study examined whether contextual social deprivation – variously based on living in a house without a car, that was overcrowded, or had an unemployed member (s) – had an independent association with SHS exposure at both individual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The present study revealed that the respondents from a low-income group had a higher risk of experiencing SHS exposure within MUH complexes compared to those from a high-income group. Similar findings have been observed in previous studies conducted in China, Kuwait, and the United States of America [ 31 33 ]. One possible explanation for this higher prevalence of SHS exposure is that households with a low income live in small flats where one room is attached to another so closely that non-smoking family members are easily exposed to tobacco smoke when other members smoke inside flats [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that the respondents from a low-income group had a higher risk of experiencing SHS exposure within MUH complexes compared to those from a high-income group. Similar findings have been observed in previous studies conducted in China, Kuwait, and the United States of America [ 31 33 ]. One possible explanation for this higher prevalence of SHS exposure is that households with a low income live in small flats where one room is attached to another so closely that non-smoking family members are easily exposed to tobacco smoke when other members smoke inside flats [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%